2018
DOI: 10.3390/polym10030309
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Drug Loading of Multiresponsive p[NIPAm-co-PEGMA] (core)/p[NIPAm-co-AAc] (Shell) Nanogels with Monodisperse Size Distributions

Abstract: We report the synthesis and properties of temperature- and pH-responsive p([NIPAm-co-PEGMA] (core)/[NIPAm-co-AAc] (shell)) nanogels with narrow size distributions, tunable sizes and increased drug loading efficiencies. The core-shell nanogels were synthesized using an optimized two-stage seeded polymerization methodology. The core-shell nanogels show a narrow size distribution and controllable physico-chemical properties. The hydrodynamic sizes, charge distributions, temperature-induced volume phase transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Their synthesis, structure, swelling characteristics, , as well as their interaction with metal ions, small organic molecules, surfactants, , biomolecules, and nanofibers have been investigated in detail. This wide interest is not surprising in the light of the large number of suggested applications, including drug delivery, emulsion stabilization, sensing, cell encapsulation, lubrication, microgel-supported catalysis , as well as their application in the fundamental studies of, e.g., flow behavior , or glass formation, , and as a building block in macroscopic hierarchical structures. , …”
Section: Introductionmentioning
confidence: 99%
“…Their synthesis, structure, swelling characteristics, , as well as their interaction with metal ions, small organic molecules, surfactants, , biomolecules, and nanofibers have been investigated in detail. This wide interest is not surprising in the light of the large number of suggested applications, including drug delivery, emulsion stabilization, sensing, cell encapsulation, lubrication, microgel-supported catalysis , as well as their application in the fundamental studies of, e.g., flow behavior , or glass formation, , and as a building block in macroscopic hierarchical structures. , …”
Section: Introductionmentioning
confidence: 99%
“…Chitosan/NiPAAM, poly(N-isopropylacrylamide-co-dimethyl-γ-butyrolactone acrylate-co-acrylic acid) (poly(NDBA)), and poly(N-isopropylacrylamide-co-sodium acrylate) (PNiPAAm-co-PNaAc) are some common NiPAAM based copolymers [ 166 ]. Raju et al used a bilayer hydrogel, both layers consisting of NiPAAM-based copolymers, and reported good encapsulation efficiency with L-DOPA [ 167 ]. Dosmar et al reported similarly good encapsulation (>84%) with vancomycin and demonstrated the biocompatibility of PEG-NiPAAM hydrogels [ 145 ].…”
Section: Materials Interactionsmentioning
confidence: 99%
“…Dual stimuli‐responsive nanogels generally involve a combination of redox‐responsive cross‐linkers and pH‐responsive polymeric matrix as important nanogel constituents. Some of the important examples of pH‐responsive polymers are polyacrylamide (PAAm), poly(acrylic acid) (PAA), PMAA, poly(2‐diethylaminoethyl methacrylate) (PDEAEMA), polyethyleneimine, poly( l ‐lysine), poly(2‐vinyl pyridine) (P2VP), poly( N ‐vinylamine) (PVAm), poly(4‐vinyl pyridine) (P4VP), and chitosan . The pH‐ and redox‐responsive nanogels hold excellent potential and play a diverse role for targeted intracellular release of drugs due to their multidimensional role in response to variation in GSH concentration and pH inside the cellular compartment.…”
Section: Dual and Triple Stimuli‐responsive Nanogelsmentioning
confidence: 99%